Political And Economic Relations Between Iran And The United States From 1961 To 1981 - Shirkhanloo, Masoumeh (2008)
The history of the relationships between these two countries does not go further than half a century ago, although it has the most variable and discrete ones. Regardless of the ways that these two countries are behaving now, reading and searching over their political and economical relationship in the past, could give us a very clear perspective of each side’s point of view. In the present study, secondary data, which were gathered from a wide range of books, journal papers and newspaper articles, were used to investigate the Iran-USA relationship in order to understand the roots of the earthquake in the USA, and Iran’s relationship from the political view, as well as the reasons why Ayatollah Khomeini and his successors had taken over the power and brought Iranian people into an anti-Shah manner. This research concentrated on the various aspects of the previous imperial of Iran, such as Mohammadreza Pahlavi (who was also known as Shah), his aspiration as a young king, his ruling in the area and his popularity in Iran.The Iranian domestic affairs, opposite groups, intelligent services and other conditions, which had bought the Islamic regime into the power, were also considered in this study. In the conclusion, the researcher found that Shah’s dependency on the USA misconceptions, unrealistic ambitions about the Iranian society and also the hegomonistic desire of supremacy power, made him a dictator and ironically brought his regime to a misfortunate end. His misunderstanding and intolerance towards any objection, gave the oppositions the time to gather around Ayatollah Khomeini and finally replace the last monarchy of Iran by the Islamic regime. This research also dedicated that the downfall of the Shah’s regime, apart from the roles of the USA was the result of his own actions as well as all the oppositions and activists’ who did not believe in Shah as the rightful governor of the country.